Electromagnetic Metal Forming for Advanced Processing Technologies - Batygin, Yuriy; Barbashova, Marina; Sabokar, Oleh.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book focuses on the new direction of magnetic pulsed metal working by attraction of sheet metals. In the first part, the authors focus on the magnetic pulsed pressure for forming of inner angles in the sheet metals. Part 2 of the book presents the magnetic pulsed attraction of thin-walled metals. In the third and last part, the authors present the practical realization of external restoring the dents on the car bodies by electromagnetic metal forming attraction.
The Magnetic Pulsed Pressure for Forming of Inner Angles in the Sheet Metals -- The Magnetic Pulsed Attraction of Thin-Walled Metals -- The practical realization of external restoring the dents on the car bodies by the EMF attraction.
Keywords: Metals; Manufactures; Surfaces (Technology).; Thin films; Metals and Alloys; Machines, Tools, Processes; Surfaces, Interfaces and Thin Film